La Santa delle cause perse e dei casi impossibili: usi artistici dell’ex-voto in 'Ex-voto offert au sanctuaire de Sainte-Rita de Cascia' di Yves Klein e 'I miracoli di Val Morel' di Dino Buzzati - Galeano, Giovanni (Incontri. Rivista europea di studi italiani, 2018)
The Saint of the Desperate Cases and Lost causes: Artistic Uses of the ex-voto in Ex-voto offert au sanctuaire de Sainte-Rita de Cascia by Yves Klein and I Miracoli di Val Morel by Dino BuzzatiThis article presents a comparative study onYves Klein’s Ex-voto offert à Sainte-Rita de Cascia and Dino Buzzati’s I miracoli di Val Morel. Firstly, it discusses how the votive forms of ex-voto circulate in contemporary art, following previous researches on the insertion  of  non-artistic  elements  in  art by Julius  von  Schlosser and Georges  Didi-Huberman. Secondly, it accounts for the interpretation of ex-voto as a performative art in a comparative analysis of Klein’s and Buzzati’s artworks. Finally, with a focus on Il colombre by Buzzati and the offert composed by Klein, it draws conclusions on the transformation of the ex-voto from devotional to contemporary art forms in both authors.